Integration of Interpersonal Space and Shared Workspace: ClearBoard Design and Experiments - Ishii, Hiroshi; Kobayashi, Minoru; Grudin, Jonathan (ACM Transactions on Information Systems, 1993)
We describe the evolution of the novel shared drawing medium ClearBoard which was designed to seamlessly integrate an interpersonal space and a shared workspace. ClearBoard permits coworkers in two locations to draw with color markers or with electronic pens and software tools while maintaining direct eye contact and the ability to employ natural gestures. The ClearBoard design is based on the key metaphor of “talking through and drawing on a transparent glass window.” We describe the evolution from ClearBoard-1 (which enables shared video drawing) to ClearBoard-2 (which incorporates TeamPaint, a multiuser paint editor). Initial observations and findings gained through the experimental use of the prototype, including the feature of “gaze awareness,” are discussed. Further experiments are conducted with ClearBoard-O (a simple mockup), ClearBoard-1, and an actual desktop as a control. In the settings we examined, the ClearBoard environment led to more eye contact and potential awareness of collaborator’s gaze direction over the traditional desktop environment.